"Ukraine is friend-or foe": identification space of fairy tales by Leonid Poltava and Vasyl Symonenko (Literatures of the World: Poetics, Mentality and Spirituality, 2017)
This article analyzes genre features of fairy tales by Vasyl Symonenko «King Plaksiy and Loskoton», «Journey to Vice Versa country» and Leonid Poltava «The tale of the Villain Sorcerer, Ivasyk Cossack and the Black Sea». Allegorical tales are investigated through the prism of the «native and alien Ukraine» concept. Identity problem is covered on the following levels, such as existential, axiological and poetic one. The existential level defines the problem of alienation in the life writing of above mentioned writers (dissident and expatriate). The axiological level sets the value system in the poetic world of both writers including the concepts of Ukraine, native land, native people, language.
Keywords: fairy tale; diaspora literature for children and youth; native-allien-another